THE INFLUENCE OF THE PROBLEM BASED LEARNING MODEL ON THE LEARNING OF ACHIEVEMENTS TO IMPROVE STUDENTS' THINKING ABILITY - Ainun, Nur; Budio, Sesra; Sar'an (Mandeh : Jurnal Pendidikan Islam, 2025)
This research is motivated by the low thinking ability of students in the teaching and learning process where students only receive information or knowledge from an educator without wanting to issue assumptions, ideas or opinions. Students will be required to have good thinking skills, if students have good abilities, then students can choose and sort out the correct information. This research aims to: Know the application of the problem based learning model to the learning of aqidah and morals at the Islamic Boarding School of Madrasah Aliyah Muhammadiyah Tamiang Ujung Gading, Know the thinking ability of students in the learning of aqidah and morals at the Islamic Boarding School of Madrasah Aliyah Muhammadiyah Tamiang Ujung Gading, Know the influence of the problem based learning model on the learning of aqidah and morals to improve students' thinking abilities at the Islamic boarding school of Madrasah Aliyah Muhammadiyah Tamiang Ujung Gading. This research is motivated by the low thinking ability of students in the teaching and learning process where students only receive information or knowledge from an educator without wanting to issue assumptions, ideas or opinions. Students will be required to have good thinking skills, if students have good abilities, then students can choose and sort out the correct information. This type of research is quantitative research with a sample of 40 respondents. The data collection methods used in this study are questionnaires, documentation and observation. Data processing is carried out using SPSS 24.0 software for validity, reliability, simple regression analysis, hypothesis testing and descriptive analysis. Based on the results of this study it can be concluded that the application of the problem based learning model at the Islamic boarding school of Madrasah Aliyah Muhammadiyah Tamiang Ujung Gading has a significant impact on students' thinking skills in learning aqidah akhlak as evidenced by the t-count and t-table values ​​of the Problem-Based Learning Model Variable (X) of (2.822> 2.02439) or sig (0.052> 0.05). This means that H0 is rejected and Ha is accepted. The coefficient of determination (R Square) is 0.017, which means that the Problem Based Learning Model variable has an effect on Thinking Ability.